2016
DOI: 10.4111/icu.2016.57.2.94
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of sepsis prior to prostate biopsy

Abstract: PurposeUrosepsis is the most feared complication of transrectal prostate biopsy. The incidence may be increasing from <1% to 2%–3% in contemporary series. Historically, fluoroquinolones have been effective antibiotic prophylaxis to prevent infective complications but antibiotic resistance is increasing. The increase in antibiotic resistance may contribute to reported increases in urosepsis and hospitalization after transrectal biopsy. This article will review other methods clinicians may employ to reduce the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…However, there are complications associated with the use of TRUSPB. Most notably, because the procedure is performed via the rectum, there is a risk of postprocedural sepsis; the incidence of sepsis ranged was 2% to 4% in contemporary series, 4,5 and sepsis-related mortality has also been reported. 6 An increasing number of studies have demonstrated success in cancer diagnosis with extended biopsy using transperineal ultrasoundguided prostate biopsy (TPUSPB).…”
Section: Implications For Clinical Practice or Policymentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are complications associated with the use of TRUSPB. Most notably, because the procedure is performed via the rectum, there is a risk of postprocedural sepsis; the incidence of sepsis ranged was 2% to 4% in contemporary series, 4,5 and sepsis-related mortality has also been reported. 6 An increasing number of studies have demonstrated success in cancer diagnosis with extended biopsy using transperineal ultrasoundguided prostate biopsy (TPUSPB).…”
Section: Implications For Clinical Practice or Policymentioning
confidence: 99%
“…10 Some authors have suggested that TPUSPB may be performed without antibiotic prophylaxis, thus reducing the risk of generating antibiotic resistance. 4 Based on these potential benefits, our centre introduced TPUSPB beginning in January 2018. Subsequently, we have completely replaced TRUSPB with TPUSPB.…”
Section: Implications For Clinical Practice or Policymentioning
confidence: 99%
“…Electronic medical records of all patients were reviewed for demographic, clinical and microbiological data. Clinical information included emergency consultations, hospital admissions and risk factors for post-PNB infection distributed into comorbidities, infectious and urological risk factors 3,4,7,10,13 . Microbiological data included available midstream-voided urine and blood cultures as well as the pathogens and antibiotic susceptibility testing, as reported by clinical microbiological laboratories.…”
Section: Data Collectionmentioning
confidence: 99%
“…Recent studies report rising rates of post-PNB infections associated with emergent FQ resistant E. coli and extended-spectrum -lactamase producing E. coli (ESBL), raising concerns about efficacy of these antibioprophylaxis regimens 2,[4][5][6] . On the other hand, various mitigating strategies are suggested in the literature: rectal swab screening with directed antibioprophylaxis 7,8 , switching antibioprophylaxis 7,[9][10][11] and transperineal biopsy approach 2,7 . Recently, some authors pointed out fosfomycin tromethamine (FOS) as being an attractive alternative, because of its adequate levels in prostatic tissue obtained with a single 3g oral dose, the low level of bacterial resistance, its broad spectrum of activity including multidrug resistant organisms, and its good safety profile [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Various techniques have been proposed, but as yet, the evidence to support these interventions is limited. A systematic review published by Toner and colleagues 7 suggested that at present, there is little evidence to support the use of simple techniques such as cleansing or disinfecting enemas or needle disinfection to decrease prostate biopsy-associated sepsis rates. Toner and colleagues suggested, however, that there is some evidence to support the efficacy of augmented antibiotic prophylaxis, targeted antibiotic prophylaxis, and use of the transperineal method to decrease rates of prostate biopsy-associated infection.…”
Section: Introductionmentioning
confidence: 99%